Characterization of the mid-infrared wavelength dependent loss in hollow core photonic crystal fibers - Harner, Mary (Kansas State University, 2015)
This research sought to characterize the length dependent loss of hollow core photonic crystal fibers (HC-PCF) in the mid-infrared. These fibers are used in gas-filled fiber lasers that operate in the mid-infrared range. A black body source which provided a broad mid-infrared spectrum was coupled into a HC-PCF and a fiber cut-back method was implemented to make the length dependent loss measurement. A monochromator was used to observe narrow bands of the broad spectrum provided by the black body source and the loss as a function of wavelength was constructed. The loss for four unique HC-PCF fibers was characterized across the wavelength range [lambda] =1754 nm to [lambda] =3220 nm. The best fibers demonstrated a loss of less than 2 dB/m across this range, with some fibers even exhibiting loss below 1 dB/m.
Keywords: optics; fiber; hollow core; mid-infrared; loss; length dependent; Atomic Physics (0748); Physics (0605)